Pre-treatment with glutamine reduces genetic damage due to cancer treatment with cisplatin - Oliveira, R. J. (2013)
Cisplatin is an effective antineoplastic drug. However, it provokes considerable collateral effects, including genotoxic and clastogenic activity. It has been reported that a diet rich in glutamine can help inhibit such collateral effects. We evaluated this activity in 40 Swiss mice, distributed into eight experimental groups: G1 - Control group (PBS 0.1 mL/10g body weight); G2 - cisplatin group (cisplatin 6 mg/kg intraperitoneally); G3, G4, G5 - glutamine groups (glutamine at 150, 300, and 600 mg/kg, respectively; orally); G6, G7, G8 - Pre-treatment groups (glutamine at 150, 300, and 600 mg/kg, respectively; orally and cisplatin 6 mg/kg intraperitonially). For the micronucleus assay, samples of blood were collected (before the first use of the drugs at T0, then 24 (T1) and 48 (T2) hours after the first administration). For the comet assay, blood samples were collected only at T2. The damage reduction percentages for the micronucleus assay were 90.0, 47.3, and 37.3% at T1 and 46.0, 38.6, and 34.7% at T2, for G6, G7, and G8 groups, respectively. For the comet assay, the damage reduction percentages were 113.0, 117.4, and 115.0% for G6, G7, and G8, respectively. We conclude that glutamine is able to prevent genotoxic and clastogenic damages caused by cisplatin.